PERAMALAN INFLASI DI INDONESIA: DYNAMIC MODEL AVERAGE - M. Rizki Nasution; Dede Ruslan; Ahmad Albar Tanjung (Media Ekonomi, 2020)
This research is to forecast inflation in Indonesia on a national scale. Forecasting use in samples and out of samples as research. Converting results using the Dynamic Dynamic Model can give results. The estimation results are carried out in the BVAR form. In forecasting using time series data for the period 2010 to 2019. Forecasting with the value of RMSE is selected in the IHK_SAND variable and another variable IHK_PROD is accepted; INF; CPI_BM; IHK_PALGBB; IHK_KES; IHK_TKJK; and IHK_MJMRT.